Dampak Penerapan International Financial Reporting Standard terhadap Investasi Langsung Asing (FDI) - Rahmat Fajar Ramdani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2019)
This research purposed to analyzing influence of implementation IFRS to foreign direct investment in Asian countries. This research used population in Asian region and sample was used in this research are from 23 countries in Asian, that used IFRS and have capital market, with observation priod for nine years observation or 207 observation, starting from 2006 to 2014. To anlyzing hyphotesis, this research used multiple linier regression dummy variabel model. The result from this research showed that implementation IFRS with modification and partial have significant and positive influence to foreign direct investment.